The Development Of Design Model Of Conflict Resolution Education Based On Cultural Values Of Pela - Samuel Patra Ritiauw (Jurnal Cakrawala Pendidikan, 2017)
Abstract: The development of conflict resolution educationbased on the cultural values of pela (CRE-BCVP) in junior high schools in Ambon is aimed to develop student’s competence in resolving conflict constructively. The model design of CRE-BCVP is derived from the local tradition of Malukucalledpela. Pela tradition containing the values of togetherness and peace is integrated with social studies education. This study used Research and Development approach developed by Borg Gall. The results of this development show that in the first stage before conducting a limited testing, the model design of CRE-BCVP gets improved in the stage of broader testing and in the final validation testing on the CRE-BCVP model. This change can be seen by excluding the third phase namely defining the conflict. In addition, the indicator of the third phase is subsequently simplified and included in the second phase namely introducing the conflict. It is aimedin order that teachers can easily and properly implement the model ofCRE-BCVP. Keywords: Model design, conflict resolution education, pela cultural values PENGEMBANGAN DESAIN MODEL PENDIDIKAN RESOLUSI KONFLIK BERBASIS NILAI BUDAYA PELA Abstrak: Pengembangan desain model PRK-BNBP yang diimplementasikan pada Sekolah Menengah Pertama di Kota Ambon bertujuan untuk mengembangkan kemampuan siswa dalam menyelesaikan konflik secara konstruktif. Pengembangan desain model PRK-BNBP bersumber dari budaya lokal masyarakat Maluku, yakni “pela”. Budaya pela yang sarat akan nilai-nilai kebersamaan dan perdamaian, diintegrasikan kedalam pendidikan Ilmu Pengetahuan Sosial. Penelitian ini menggunakan tipe penelitian dan pengembangan (Research and Development) yang dikembangkan oleh Borg Gall (2003). Adapun hasil dari pengembangan ini memperlihatkan bahwa desain model PRK-BNBP pada tahapan awal sebelum dilakukan uji terbatas, mengalami perbaikan pada tahapan uji lebih luas dan uji validasi akhir model PRK-BNBP. Perubahan tersebut dapat terlihat dari dihilangkannya fase ketiga yakni mendefinisikan konflik dan indikator fase ketiga disederhanakan dan dimasukkan ke dalam fase kedua, yakni mengenalkan konflik. Hal ini bertujuan agar guru dapat dengan mudah mengimplementasikan model PRK-BNBP dengan baik. Kata Kunci: desain model, pendidikan resolusi konflik, nilai budaya pela